Prevalence and Types of Extended-Spectrum β-Lactamase-Producing Bacteria in Retail Seafood - Ryan Pearce; Beate Conrady; Luca Guardabassi (Foods, 2023)
Objectives: To assess prevalence and types of extended-spectrum β-lactamase (ESBL)-producing bacteria in retail seafood. Methods: A literature review was completed according to international guidelines for systematic reviews, except for being performed by a single reviewer. Kruskal–Wallis and Dunn tests were used to determine statistical differences between continents or seafood types. Results: Among 12,277 hits, 42 publications from 2011 to 2023 were deemed relevant to the review’s objectives. The median prevalence of ESBL-contaminated products was 19.4%. A significantly lower prevalence was observed in Europe (p = 0.006) and Africa (p = 0.004) compared to Asia. Amongst the 2053 isolates analyzed in the selected studies, 44.8% were ESBL-positive. The predominant type was CTX-M (93.6%), followed by TEM (6.7%) and SHV (5.0%). Only 32.6% and 18.5% of the CTX-M-positive isolates were typed to group and gene level, respectively. While group 1 (60.2%) was prevalent over group 9 (39.8%) among Enterobacterales, the opposite trend was observed in Vibrio spp. (60.0% vs. 40.0%). Information at gene level was limited to Enterobacterales, where CTX-M-15 was the most prevalent (79.2%). Conclusions: On average, one in five seafood products sold at retail globally is contaminated with ESBL-producing Enterobacterales of clinical relevance. Our findings highlight a potential risk for consumers of raw seafood, especially in Asia.